P11.01.B Lower-extremity deep vein thrombosis and bleeding complications in primary brain tumor patients: A prospective study. (5th September 2022) - Muster, V; Raggam, R B; Urbanic-Purkart, T; Posch, F; Gütl, K; Rabensteiner, J; Prüller, F; von Campe, G; Rief, M; Brodmann, M; Gary, T
Abstract: Background: P rimary brain tumor patients have a high risk of venous thromboembolism (VTE). Bleeding risk with prophylactic and therapeutic anticoagulation is an important concern in these patients, and data on the management of asymptomatic VTE events in this population are lacking. The aim of this prospective study is to investigate risk and risk factors for asymptomatic lower-extremity deep-vein thrombosis (LE-DVT) in patients with primary brain tumors, and to estimate the rate of bleeding complications on full, prophylactic or no anticoagulation. Material and Methods: We included consecutive patients with primary brain tumours undergoing surgery. Screening for asymptomatic LE-DVT by compression ultrasound (CUS) was performed pre-operatively and postoperatively within 2 months after surgery. Telephone follow-up was done 6 and 12 months after surgery. The protocol pre-specified therapeutic doses of low-molecular-weight heparin (LMWH) in case of detection of an asymptomatic LE-DVT. Results: Fifty patients were included (female: 34%, median age 58 years, WHO grade IV tumors: 78%, prophylactic-dose LMWH at baseline: 12%). During a median observation period of 9.1 months, LE-DVT was detected in 9 patients (18%). LE-DVTs included two asymptomatic events (4%) at pre-operative screening, five asymptomatic events (10%) at postoperative screening, and two symptomatic events (4%, both 4-level LE-DVT) at telephone follow-up. This corresponded to a 12-month cumulative incidence of LE-DVT of 14.9% (95%CI: 6.4-26.6). At postoperative screening, n=10 patients were on prophylactic-dose LMWH, and one of these patients had an LE-DVT event detected by screening. The two patients with symptomatic LE-DVT were not on thromboprophylaxis at the time of event. Among a variety of investigated potential risk factors, only higher age (Odds Ratio (OR) per 5 years increase=1.46, 95%CI: 1.01-2.13, p=0.05), higher neurologic assessment in neuro-oncology (NANO) scale (OR per 1 point increase=1.59, 1.00-2.54, p=0.05), higher serum Galectin-3 levels (OR per 1ng/ml increase=1.20, 1.01-1.42, p=0.041) but not D-Dimer (OR per 1mg/L increase=1.89, 0.75-4.77, p=0.178) emerged as significant predictors of any LE-DVT. Six patients (12%) developed bleeding events, including n=3 operative intracranial bleedings without LMWH, n=1 spontaneous ventricular hemorrhage without LMWH, n=1 minor subcutaneous bleeding without LMWH, and 1 intracerebral hematoma during therapeutic-dose LMWH initiated for asymptomatic distal LE-DVT. Conclusion: In our study we detected a high-frequency of asymptomatic LE-DVT in patients with primary brain tumours. Conversely, symptomatic LE-DVT risk was low, which may be related to prior screening. Patients with primary brain tumors appear to have LE-DVT risk factors specific to this entity. Prophylactic-dose LMWH did not show any adverse safety signals regarding bleeding.